Comparing Effects of Two Different Explicit–Reflective Instructions on Pre-School Prospective Teachers’ View about Nature of Science and Scientific Knowledge - Mustafa Metin (Journal of Science Learning, 2022)
This study aims to compare the effect of formative assessment with explicit-reflective instruction and explicit-reflective on pre-school prospective teachers' views about the nature of science and scientific knowledge. In this study, it was used a pretest-posttest nonequivalent control group design and the sample of the study consists of 66 pre-school prospective teachers in the 2nd grade. There are 33 of them were assigned control group and the others were assigned as the experimental group. Since the students could not be randomly grouped in the study, a quasi-experimental design was used. In this study, the nature of science scale (NOSS) and the attitude scale towards scientific knowledge (SKS) were used as pre-test, post-test and retention test.  In order to teach the students by using nature of science (NOS) and scientific knowledge (SK), open-reflective instruction was used in the control group, and open-reflective instruction and embedded formative assessment were applied in the experimental group. NOSS and SKS were used as a pre-test, post-test and retention-test in this study. In order to teach the students NOSS and SK, while Explicit-reflective instruction was applied in the control group, formative assessment embedded with Explicit-reflective instruction was applied experimental group.As a result of the study, it was determined that the formative assessment embedded with Explicit-reflective instruction was more positively and permanently changed on pre-school prospective teachers' view about NOS and SK than the other method